2012
DOI: 10.3109/14017431.2012.731518
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative NT-proBNP independently predicts outcome in patients with acute coronary syndrome undergoing CABG*

Abstract: Preoperative NT-proBNP predicted in-hospital mortality, severe circulatory failure postoperatively and long-term survival in patients undergoing surgery for acute coronary syndrome but a higher threshold was found in patients having concomitant procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 17 publications
4
19
0
2
Order By: Relevance
“…The mechanism involved in NT-proBNP release in ischemia is not entirely clear 120 , although Xu et al observed a relationship between NT-proBNP and CAD severity 121 . The results of our study supported previous findings that showed that, in cardiac surgery, NT-proBNP levels were associated with morbidity and mortality [122][123][124][125][126] . In contrast to other studies, we found that the ability of NT-proBNP to predict severe PHF was less convincing in the context of AS 108 .…”
Section: Nt-probnp and Phfsupporting
confidence: 92%
“…The mechanism involved in NT-proBNP release in ischemia is not entirely clear 120 , although Xu et al observed a relationship between NT-proBNP and CAD severity 121 . The results of our study supported previous findings that showed that, in cardiac surgery, NT-proBNP levels were associated with morbidity and mortality [122][123][124][125][126] . In contrast to other studies, we found that the ability of NT-proBNP to predict severe PHF was less convincing in the context of AS 108 .…”
Section: Nt-probnp and Phfsupporting
confidence: 92%
“…SubP gave higher specificity (83%) and sensitivity (80%) than NT-proBNP which was reported as an early marker candidate for the diagnosis of AMI patients in many groups. 10,21,27 From above results, we suggested SubP and NPY as early diagnostic biomarkers for AMI patients. The combination of two peptides analysis will give a chance to find for AMI patients in early stage.…”
Section: Resultsmentioning
confidence: 99%
“…21,25 Unfortunately, the area under the receiver operating characteristic (ROC) curve was below 70% and sensitivity and specificity values were below 80%. 26,27 Therefore, the development of a more sensitive and specific diagnostic biomarker is necessary for the early diagnosis of AMI.…”
Section: Introductionmentioning
confidence: 99%
“…Preoperative levels of its sister compound, brain natriuretic peptide (BNP), have been used to predict postoperative mortality in patients undergoing cardiac surgery procedures, including CABG 41, 42. Additionally, studies on patients undergoing isolated CABG found associations between preoperative levels of NT‐ProBNP and postoperative mortality, prompting inclusion of preoperative levels of the biomarker into our models 16, 43, 44…”
Section: Discussionmentioning
confidence: 99%